If the boot fits [large type] - Witemeyer, Karen (Witemeyer, Karen. Texas ever after., 2024)
"Determined to prove that cattle king Eli Dearing has no justification for evicting his stepmother and half brothers, Asher Ellis uses the cover of a fancy ball to break into the Three Cedars ranch house to search for proof of wrongdoing. On the verge of discovery, he flees, but a boy's cry compels him to make a daring rescue. Spunky and independent, Samantha Dearing balks when she learns the ball her father is hosting in her honor is nothing more than a matrimonial ambush. Taking a break from her unwanted suitors, Samantha spots a thief fleeing her home. When the stranger ends up saving her brother's life, she hides the only clue to his identity left behind--his boot--and resolves to find him herself. But when Samantha encounters the older brother of a student she tutors, all thoughts of the bootless mystery man vanish. And although Asher tries to keep his distance from Samantha for reasons of his own, a series of suspicious accidents befall her, and his protective instincts flare, no matter the cost to their future."--